2022
DOI: 10.3390/jcm11051375
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Nonalcoholic Fatty Liver Disease and Type 2 Diabetes Mellitus

Abstract: The incidence of nonalcoholic fatty liver disease (NAFLD) is growing worldwide. Epidemiological data suggest a strong relationship between NAFLD and T2DM. This is associated with common risk factors and pathogenesis, where obesity, insulin resistance and dyslipidemia play pivotal roles. Expanding knowledge on the coexistence of NAFLD and T2DM could not only protect against liver damage and glucotoxicity, but may also theoretically prevent the subsequent occurrence of other diseases, such as cancer and cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 189 publications
(210 reference statements)
0
16
0
Order By: Relevance
“…Carduus acanthoides anti-diabetic investigations provided similar results in the past [ 27 ]. Aminotransferase levels tend to rise in patients with diabetes and are more common than in the general population [ 28 ]. After the introduction of alloxan in prior research, there was a large rise in the activity of specific enzymes, such as Beta-Glucuronidase, Nacetyl-bet Glucosaminidase, Leucine Aminpeptidase, Lysosomal Acid Phosphates, and Cathepsin D [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carduus acanthoides anti-diabetic investigations provided similar results in the past [ 27 ]. Aminotransferase levels tend to rise in patients with diabetes and are more common than in the general population [ 28 ]. After the introduction of alloxan in prior research, there was a large rise in the activity of specific enzymes, such as Beta-Glucuronidase, Nacetyl-bet Glucosaminidase, Leucine Aminpeptidase, Lysosomal Acid Phosphates, and Cathepsin D [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that obesity coupled with insulin resistance and type 2 diabetes are common comorbidities that exacerbate the progression of NAFLD in a clinical setting. In the insulin-resistant state, hepatic glucose production and fatty acid uptake are elevated, leading to increased substrates for triglyceride synthesis [40]. The fact that PRR antagonism was unable to alter body weight, fasting blood glucose or glucose handling in HFD-fed mice may suggest that our intervention only targets enzymatic pathways directly involved in lipid synthesis while leaving other clinical aspects of NAFLD pathology unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The authors used the logistic regression models on the collected dataset for conducting the study. Kosmalski et al (2022) [33] found that there is an underestimation of the liver disease problem in diabetic people and showed the coexistence of both the diseases. The authors alleged that glucose metabolism disturbances diagnosis is typically not performed in patients having liver disease.…”
Section: Bhowmik Et Al (2018) [26] Studied the Ruralmentioning
confidence: 99%